Evaluation of Front Line Demonstration on Mustard Crop in Rohtak District of Haryana - Sangwan, Meenakshi; Singh, Jagat; Pawar, Neeraj; Siwach, Meena; Solanki, Y.P.; Ramkaran (Indian Journal of Extension Education, 2021)
Cluster frontline demonstrations on mustard crop covering 114.4 ha area under mustard using variety RH 0749 were carried out by Krishi Vigyan Kendra at 261 farmers’ fields in Rohtak district of Haryana state during three consecutive kharif seasons 2017-18 to 2019-20. The critical inputs were identified in existing crop production technology through farmers meetings and group discussions. The findings showed significant increase in the average yield of demonstrated plot (12.4%) over the control plot of mustard crop. Considerably lower yield was observed under farmer’s practices because of considerable gap/variation in the extent of adoption of recommended technology. Average extension gap, technology gap and technology index of mustard crop was found 229 kg/ha, 1423 kg/ha and 40.63 per cent, respectively. Three years average yield, net returns and benefit: cost ratio (BCR) in demonstrated plots came out to be 2076 kg/ha, Rs. 51549 Rs/ha and 2.9, respectively which was significantly higher than local check with average yield 1846 kg/ha, net returns 43366 Rs/ha and BCR 2.74. The higher yield and returns in demonstrations indicated that productivity of mustard at farmers’ fields could be increased by adopting improved technologies. Hence, FLDs showed positive effects of production and protection technologies in mustard crop.
Keywords: Adoption; Cluster frontline demonstration; Impact; Mustard; Net returns; Technological gap